MPC with Space Vector Phase-Shift PWM (SV-PSPWM) Technique with Harmonic Mitigation Strategy for Shunt Active Power Filters Based on H-Bridge Multilevel Converter - Renault, Alfredo; Pacher, Julio; Comparatore, Leonardo; Ayala, Magno; Rodas, Jorge; Gregor, Raul (Frontiers in Energy Research, 2022)
This article presents a model predictive current control of a shunt active power filter based on 7-level cascaded H-bridge converters. By using the spacial vector modulation approach into the model predictive control, a considerable reduction of the computational burden is achieved and makes possible the real-time implementation in a custom experimental setup. Then, the current harmonics on the grid side, caused by non-linear loads connected to the point of common coupling, are compensated. The experimental results confirmed the feasibility and efficacy of the proposed controller.